2022
DOI: 10.1200/jco.2022.40.6_suppl.028
|View full text |Cite
|
Sign up to set email alerts
|

Racial disparity in survival of African-American (AA) patients diagnosed with metastatic prostate cancer: Analysis of surveillance epidemiology and end results program.

Abstract: 28 Background: Amongst all cancers in men, prostate cancer (PCa) is the most common cancer, and the second leading cause of death. Racial disparities in PCa care in the United States (US) are known to exist. However, it is not clear if this disparity is also noted specifically in patients diagnosed with metastatic PCa (metaPCa). We analyzed the Surveillance Epidemiology and End results Program (SEER) 18 registry, to determine the racial disparity in survival of AA patients diagnosed with metaPCa compared to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Of the 62 records, 47 were full-text publications [ 3 , 20 65 ] and 15 were conference abstracts [ 66 – 80 ]. The 54 unique studies consisted of 53 cohort studies [ 3 , 20 62 , 64 , 65 , 70 , 71 , 73 , 77 – 80 ] and 1 case control study [ 63 ]. Of these, 50 studies were retrospective [ 3 , 20 31 , 33 41 , 43 63 , 65 , 70 , 71 , 73 , 78 – 80 ], 3 were prospective [ 42 , 64 , 77 ], and 1 was mixed (prospective and retrospective) [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the 62 records, 47 were full-text publications [ 3 , 20 65 ] and 15 were conference abstracts [ 66 – 80 ]. The 54 unique studies consisted of 53 cohort studies [ 3 , 20 62 , 64 , 65 , 70 , 71 , 73 , 77 – 80 ] and 1 case control study [ 63 ]. Of these, 50 studies were retrospective [ 3 , 20 31 , 33 41 , 43 63 , 65 , 70 , 71 , 73 , 78 – 80 ], 3 were prospective [ 42 , 64 , 77 ], and 1 was mixed (prospective and retrospective) [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…The 54 unique studies consisted of 53 cohort studies [ 3 , 20 62 , 64 , 65 , 70 , 71 , 73 , 77 – 80 ] and 1 case control study [ 63 ]. Of these, 50 studies were retrospective [ 3 , 20 31 , 33 41 , 43 63 , 65 , 70 , 71 , 73 , 78 – 80 ], 3 were prospective [ 42 , 64 , 77 ], and 1 was mixed (prospective and retrospective) [ 32 ]. Research reported in these studies was conducted in the United States (US) ( n = 51) [ 3 , 20 27 , 29 61 , 63 65 , 70 , 71 , 73 , 77 , 78 , 80 ], Europe ( n = 1) [ 62 ], Asia ( n = 1) [ 79 ], and Oceania ( n = 1) [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations